International Chinese Student’s Satisfaction Towards University Malaysia Sabah’s Nursing Mobility Program - Segaran Ramodran; Soong, Shui Fun; Cynthia Francis; Dayang Natasha; Myra Yusrrie (Malaysian Journal of Medicine and Health Sciences, 2020)
Promotion of internationalization of higher education is a strategic marketing in public and private Ma¬laysia universities.University Malaysia Sabah (UMS) hosted the international nursing mobility programme involving 15 nursing students from Hunan and Yangtze University of China. Students from China obtained hands-on learn¬ing experience and exposed to indigenous health practices in Sabah. After 12 weeks of the programme, although casual face-value audit of the mobility program was deemed adequate, there was a need to objectively gauge the Chinese student’s satisfaction and identify issue of contention that can be remedied. This study is to evaluate Chi¬nese international nursing students’ satisfaction during their mobility posting tenure in UMS and identify issues of discontentment for improvement. Methods: the study entailed a cross sectional survey involving a convenient sam¬ple of all 15 nursing students from China who had completed the 12-week UMS-nursing mobility programme. The study tool consisted of a 25-item questionnaire which used Likert-like statements to anchor level of satisfaction on 5 sub-domains itemsnamely; arrival orientation; logistic arrangements; learning opportunities; cultural experience and perceived worth-for-money. Results: Cumulative ratings counts from 15 Chinese international students who had participated in the UMS-nursing mobility program in this study rated the following sub-domains as satisfactory and highly satisfactory: (i) learning experience (88%), (ii) Sabah’s cultural experience (90%), (iii) worth for money (88 %). Sub-domains rated as dissatisfactory or strongly dissatisfactory by the China students were: (i) adequacy of 1st - day arrival orientation (72%), (ii) quality of logistic arrangement (72%). Conclusion: Findings imply that the China students were satisfied with the overall learning experience during the UMS-nursing mobility programme. However, areas of grievances such as the conduct of the 1st - day arrival orientation and logistics management of the UMS-mo¬bility program needs to be addressed.